Kesalehan Sosial di Era Disrupsi, Tinjauan Psikologi Salat - Ahmad Lailatus Sibyan; Eva Latipah (IDEA: Jurnal Psikologi, 2022)
The real impact of advancing technological products is the birth of a new era called the era of disruption, where various changes occur as a result of disruptions which result in changes in the system and order in people's lives in general. The emergence of the new era also affects social life. Included in this is the social impact of building social piety in prayer services. This study uses library research, namely by solving contextual theory problems by collecting and compiling various sources from various sources such as books, journals, magazines, websites, newspapers, and so on. The results of this study state that social disruption in the era of disruption can be increased through prayer. Prayers have an important position in Islam, especially those that are performed in the congregation. Congregational prayers besides having many rewards also have various benefits both personal and social. Congregational prayers also contain psychological aspects including aspects of communication, a sense of being cared for and meaningful, a feeling of togetherness, no personal distance, and environmental therapy. From a psychological perspective, prayer is not only able to increase individual ritual piety but is also able to increase social piety.